Compound Cocktail Inhibits Influenza Viral Pneumonia via Phospholipase Cγ1 Phosphorylation-Related Necroptosis and Partial Autophagy in Natural Killer Cells - Ma, Rong; Ma, Rui-Qing; Chen, Bei; Wang, Li-Yu; Fan, Xiao-Yong (Planta Medica, 2021)
Influenza viral infections are prone to global outbreaks and cause pneumonia in affected populations. High morbidity and mortality caused by pneumonia occur during an influenza pandemic. Antivirals or control of inflammation is the primary means of influenza treatment. A compound cocktail composed of arctiin, daidzein, glycyrrhizic acid, and liquiritin inhibited mouse pneumonia resulting from a PR8 viral infection and caused a weight gain after oral administration. Natural killer cell activating receptors, both Ly49D and Ly49H in the lungs, were increased in the treatment in mice. In H3N2 virus-infected natural killer-92MI cells, the cocktail treatment had different effects on phosphorylation sites of phospholipase Cγ1 (PLCγ1) and killed infected cells through necroptosis or late apoptosis, in which RIP3 was increased and both caspase-3 and phosphorylated-JNK in the cells were downregulated. Acid phosphatase activity in viral-infected natural killer-92MI cells was induced by the compound cocktail treatment, which could be related to the p62 decrease in natural killer-92MI cells. In addition, an autophagic flux induction was observed in alveolar basal epithelial cells (A549). Protein p65, but not phosphorylated-p65, was significantly decreased by the treatment. Our results indicate that the compound cocktail strengthened the phosphorylation of PLCγ1-related necroptosis and partial autophagy in natural killer cells, which could yield an inhibitory effect on viral pneumonia in influenza.
Keywords: compound cocktail; natural killer cell; PLCγ1; necroptosis; acid phosphatase; autophagy